Análise de condutas unilaterais anticoncorrenciais na nova economia: os desafios da intervenção antitruste no caso de exercício abusivo de posição dominante em negócios baseados na internet - Andre Costa Ferreira de Belfort Teixeira (2017)
This paper aims at analyzing the interface between antitrust policy and the New Economy, specifically regarding unilateral anticompetitive practices by internet based businesses. During the antitrust investigations against Microsoft and Google, based on signs of abusive exercise of dominant position through unilateral practices, antitrust intervention in New Economy markets faced several challenges, including defining the relevant markets involved, analyzing the existence and abusive exercise of market power, and creating effective antitrust remedies. This research therefore sets to understand the reasons for these challenges. In order to approach the underlying issues, this work is divided into three parts. The first part examines the architecture of the Internet as a network, in order to deepen knowledge about its technical aspects. The second part analyzes the New Economy, its definition, its defining elements, and how it differs from the previous economic paradigm. The third and last part analyzes the competitive dynamics in the internet economy, the behavior of its agents, and what challenges classic competitive concepts have faced when applied to this economy. Finally, the paper analyzes some antitrust cases against Microsoft and Google, in order to test the applicability of the issues identified during the theoretical analysis. The paper concludes that the tools used to analyze and identify anticompetitive behavior and the subsequent antitrust intervention appear to be ineffective in at least some cases of the internet economy, indicating the need to develop new tools or approaches for such cases.